2019
DOI: 10.32481/djph.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Four Decades of Epidemiologic Science on HIV Infection and Disease, and Its Impact on Public Health Practice and Policy for Sexual and Gender Minority Persons

Abstract: Even at the cusp of the second decade of the new millennia, HIV continues to be a significant public health challenge for sexual and gender minorities (SGM). Men who have sex with men and transgender women, in particular, continue to report higher rates of HIV incidence compared to their heterosexual counterparts, while facing significant barriers to comprehensive sexual healthcare. In Delaware, HIV infection impacts a substantial number of individuals with approximately 14.5 incident cases per 100,000. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Owing to exposures during anal intercourse, the prevalence of human immunodeficiency virus (HIV) among men who have sex with men (MSM) is significant ( Assi et al., 2019 ; Tran and Welles, 2019 ). Indeed, a recent study on MSM in China showed that their odds of HIV infection have trended upwards over time ( Dong et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to exposures during anal intercourse, the prevalence of human immunodeficiency virus (HIV) among men who have sex with men (MSM) is significant ( Assi et al., 2019 ; Tran and Welles, 2019 ). Indeed, a recent study on MSM in China showed that their odds of HIV infection have trended upwards over time ( Dong et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%